2016
DOI: 10.1177/1535370216650292
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Metabolic alterations from early life thyroxine replacement therapy in male Ames dwarf mice are transient

Abstract: Ames dwarf mice are exceptionally long-lived due to a Prop1 loss of function mutation resulting in deficiency of growth hormone, thyroid-stimulating hormone and prolactin. Deficiency in thyroid-stimulating hormone and growth hormone leads to greatly reduced levels of circulating thyroid hormones and insulin-like growth factor 1, as well as a reduction in insulin secretion. Early life growth hormone replacement therapy in Ames dwarf mice significantly shortens their longevity, while early life thyroxine (T4) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Quantative RT-PCR was performed as previously described [ 12 ] using the StepOne System and SYBR Green master mix. In short, tissue was homogenized, RNA was extracted using an RNeasy lipid tissue mini kit following the manufacturer’s instructions, and cDNA was made using an iScript cDNA synthesis kit.…”
Section: Methodsmentioning
confidence: 99%
“…Quantative RT-PCR was performed as previously described [ 12 ] using the StepOne System and SYBR Green master mix. In short, tissue was homogenized, RNA was extracted using an RNeasy lipid tissue mini kit following the manufacturer’s instructions, and cDNA was made using an iScript cDNA synthesis kit.…”
Section: Methodsmentioning
confidence: 99%
“… 97 , 98 However, treatment of dwarf mice with thyroxine limited to the peripubertal period did not alter their longevity. 93 , 99 …”
Section: Indirect Links Between Somatic Growth and Longevitymentioning
confidence: 99%
“…(ii) Bartke and colleagues, have dealt intensively into various conditions of GH deficit and ageing (198,242) and recently reported that a short (6 weeks) phase of early exposure to GH (starting at 2 weeks age) reduced lifespan and cellular stress resistance in Ames dwarf mice (243). A parallel thyroxine treatment had no effect on lifespan (243,244,245) whereas thyroxine and GH combined treatment reduced maximal lifespan in only female Ames mice (246). (iii) Extensive work by Brown-Borg and colleagues have described epigenetic signatures in DNA methylation patterns in Ames mice compared to their WT littermates (247,248).…”
Section: Future Directions Of Lifespan Studies On Ghrko Micementioning
confidence: 99%